Conceptual design of battery energy storage for aircraft hybrid propulsion system - Rashed, Mohamed; Le Peuvedic, Jean-Marc; Bozhko, Serhiy (2016)
The paper presents a conceptual design approach for Energy Storage (ES) devices in advanced hybrid propulsion system for small aircrafts. The study targets operational improvement and reduction of fuel consumption for different flight missions. Power sharing strategies for ES and the engine are proposed for cruise flight phase aiming to maximise the range and/or endurance for the available amount of fuel in the tank. The ES size is designed against the engine performance and the proposed power sharing strategy by optimizing the flight altitude.